Разработка виртуального уз-сканера как имитационной обучающей системы - Аврунін, О. Г.; Носова, Я. В. (ХНУРЭ, 2011)
This work is dedicated to the creation of a virtual ultrasonic scanner. It can be used to educate students to understand the physical meaning of the ultrasonic scan. The developed program has a friendly interface and easy to use. Advantage of this program is the possibility of quickly modify according to the modern requirements.
Keywords: диагностический прибор; биомединженер